Fatty Acid Ethyl Esters Obtained From Safflower Oil: A Fully Renewable Biofuel - Isler-Kaya, Asli; Karaosmanoglu, Filiz (ASME International, 2023)
Abstract With the aim to obtain a pure renewable second-generation biofuel, transesterification reaction of safflower oil and sugar beet molasses-originated ethanol and usage options as a blend component were investigated. Depleting fossil fuels, increasing fossil fuel prices, and fossil fuel-related emissions are significant global problems. The progress in pure bio-based and safer fuels gains importance to figure out these problems. Biodiesel is an excellent fuel candidate that can substitute conventional diesel fuel. For its production, fatty acid methyl esters were primarily proposed. However, with their many advantages, ethyl esters have come to the fore because of environmental and technical issues. Thus, using a by-product originated bioethanol as alcohol and safflower oil as a nonedible raw material would further enhance the renewability and sustainability of one of the second-generation biofuels. This article studied the transesterification reaction of safflower oil with sugar-beet molasses-originated bioethanol. The effects of the safflower oil:ethanol (mole:mole) ratio, catalyst amount, and temperature on the ester content were individually investigated. The fuel properties of safflower oil ethyl ester and 2%, 5%, and 7% v/v safflower oil ethyl ester-blended diesel and rural diesel fuels were determined according to the standards. The main advantages of ethyl ester addition to diesel fuel include the increase in flash point and the decrease in the sulfur content. However, some additives should improve some properties (cold filter plugging point and oxidation stability).